Combination of multimodal imaging features predictive of choroidal nevus transformation into melanoma - Dalvin, Lauren A; Shields, Carol L; Ancona-Lezama, David Arturo; Yu, Michael D; Di Nicola, Maura; Williams Jr, Basil K; Lucio-Alvarez, J Antonio; Ang, Su Mae; Maloney, Sean M; Welch, R Joel; Shields, Jerry A (British journal of ophthalmology, 2019)
AimTo characterise combinations of multimodal imaging risk factors and predictive value for choroidal nevus transformation into melanoma.MethodsThis is a retrospective review of multimodal imaging features for 3806 choroidal nevi from 1 January 2007 through 1 January 2017. Kaplan-Meier estimates and Cox regression analyses were used to calculate 5-year percentages of growth to melanoma and HR.ResultsUsing multimodal imaging, six risk factors predictive of choroidal nevus transformation into melanoma were identified, namely tumour thickness >2 mm, subretinal fluid, symptoms of visual acuity loss to 20/50 or worse, orange pigment, hollow acoustic density and tumour largest basal diameter >5 mm. Kaplan-Meier 5-year estimated tumour growth was found in 1% of nevi with no risk factors, 11% (range 9%–37%) with one factor, 22% (12%–68%) with two factors, 34% (21%–100%) with three factors, 51% (0%–100%) with four factors and 55% (0%–100%) with five factors. HR for growth was 0.1 with no factor, 2.1–7.8 with one factor, 1.8–12.1 with two factors, 4.0–24.4 with three factors, 4.6–170.0 with four factors and 12.0–595.0 with five factors. The highest HR with each combination of two, three, four or five risk factors always included symptoms of visual acuity loss and orange pigment.ConclusionSix risk factors for choroidal nevus transformation into melanoma by multimodal imaging have been identified. Risk for transformation into melanoma is 1% when no factors are present, and approaches 100% with specific combinations of three or more risk factors. Understanding how combinations of factors influence risk of transformation into melanoma can guide counselling and treatment decisions.